المعالجة الالكتروكيماوية والالكتروكيماوية الضوئية للمياه الملوثة لمعاصر زيت الزيتون في الساحل السوري - صالح فؤاد; الشحنة محمد; خليل مصعب (Latakia University Journal -Basic Sciences Series, 2018)
Electrochemical and photo-electrochemecal treatment of O.O.W.W was carried out to oxidize many of organic components presented in the water. The effect of anodic oxidation was determined by measuring the COD reduction for each case. The most considerable effect was reached by using anodes of CuO (65% reduction of COD) and 60% for anodes of Cu-metallic anodes, exceeding 50% for Pb-metallic anodes, compared to anodes of tin, Sn (about 25% COD reduction .) Introducing UV-A radiations was of low effect, an additional reduction was obtained with CuO anodes of 4-5 % only, while no effect had been noticed for other metallic anodes . تم استخدام المعالجة الالكتروكيماوية , والالكتروكيماوية الضوئية لأكسدة العديد من الملوثات العضوية الموجودة في مياه معاصر الزيتون . تمت عمليات تحديد أثر الأكسدة الأنودية بواسطة خفض الدليل COD (الطلب الكيماوي للأكسجين ) لكل من الحالات المدروسة . حصلنا على أكبر قيمة لخفض الدليل COD باستخدام آنودات ( مصاعد) من CuO بلغ خفض الدليل COD أكثر من 65% وإلى 60% في حال آنودات Cu , ووصل هذا الخفض حتى أكثر من 50% في حال استخدام أنودات من الرصاص , بينما حصلنا على خفضCOD بحدود 25% في حال أنودات القصدير . أدى إدخال الأشعة UV-A إلى خفض إضافي بحدود 4-5 % في حال أنودات CuO , بينما لم تؤثر UV-A في حال بقية الأنودات .